THE IMPORTANCE OF THE ASTRAGAL PLANT IN MEDICINE AND ITS EFFECT ON A HEALTHY LIFESTYLE - Zikrillaev Farrukh Abdurashitovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The main purpose of the article is to highlight in detail the role of the astragal medicinal plant in human health. Prevention of diseases of the Astragal plant is important that is, in prophylaxis , in the current period, chronic diseases hypodynamia, improper nutrition and harmful habits cause a significant increase in the cause are comprehensively confirmed, which causes the plant to deeply wrap its importance in health.